Releasing the Kraken - Salzberg, Steven L.; Wood, Derrick E. (Frontiers in Bioinformatics, 2021)
Ten years ago, the dramatic rise in the number of microbial genomes led to an inflection point, when the approach of finding short, exact matches in a comprehensive database became just as accurate as older, slower approaches. The new idea led to a method that was hundreds of times times faster than those that came before. Today, exact k-mer matching is a standard technique at the heart of many microbiome analysis tools.